Hemingway, Vittorini, and the Gramscian â€œNazionale-Popolareâ€ - Arrigoni, Carlo (Mediterranean Journal of Social Sciences, 2012)
1946 witnessed the cultural and political debate between the Italian Communist Party (PCI) and the journal â€œIl Politecnicoâ€,edited by Elio Vittorini. The PCI criticized â€œIl Politecnicoâ€ for being â€œintellectualistâ€ and for intensifying the crevice between intellectualsand the people, thus contradicting the journalâ€™s initial premises, that is, the creation of a new culture. The PCIâ€™s grounds were based onthe publication of the novel For Whom the Bell Tolls by Ernest Hemingway. The American novelist was incapable, according to the PCI,of understanding and narrating beyond his own immediate and egotistical impressions.The existing turmoil between the world of cultureand the masses constitutes one of Antonio Gramsciâ€™s fundamental themes, especially if we consider the concept of â€œnazionalepopolareâ€,which underlies the entire debate mentioned above. Persuaded that the PCIâ€™s position derives, not only from a wrongtheoretical approach, but also from a critical error in the judgment of the American writer, I will analyze the author under the light of thegramscian category of â€œnazionale-popolareâ€. My main purpose is to suggest new means of comprehending the importance ofHemingway to Vittorini and his generation (Pavese, in primis, down to Calvino), and to read under an innovative perspective therelevance of American literature to the Italian culture of the mid-twentieth century.